2019
DOI: 10.1089/cell.2018.0051
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofPeriostinSilencing on the Autophagy of Osteoblasts

Abstract: The objective of the present work was to investigate the effect of Periostin (POSTN) silencing on autophagy in osteoblasts, and provide an experimental basis for studying the mechanism of dental eruption. The cells were divided into the following four groups according to their viral number: the NC group, pFU-GW-016PSC53349-1; group KD1, LVpFU-GW-016PSC66471-1; group KD2, LVpFU-GW-016PSC66472-1; and group KD3, LVpFU-GW-016PSC66473-1. The lentiviral vector was infected at MOI = 100 in the ENi.S medium containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…In CRC, cell autonomy and non‐autonomous roles for autophagy are essential in growth and progression; however, the mechanisms downstream of autophagy to reduce or enhance tumour growth are not well known 15 . It was recently reported that autophagy protein expression levels in mouse osteoblasts were increased after PN silencing 16 . Up to present knowledge, the alterations of autophagy on CRC tumour promotion after exposure to PN are still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CRC, cell autonomy and non‐autonomous roles for autophagy are essential in growth and progression; however, the mechanisms downstream of autophagy to reduce or enhance tumour growth are not well known 15 . It was recently reported that autophagy protein expression levels in mouse osteoblasts were increased after PN silencing 16 . Up to present knowledge, the alterations of autophagy on CRC tumour promotion after exposure to PN are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…15 It was recently reported that autophagy protein expression levels in mouse osteoblasts were increased after PN silencing. 16 Up to present knowledge, the alterations of autophagy on CRC tumour promotion after exposure to PN are still unclear.…”
mentioning
confidence: 99%
“…In addition, decreased levels of LC3 have been observed following exposure to Postn 21 . The autophagic function of osteoblasts is enhanced when Postn is knocked down 22 . Consistent with previous studies, we demonstrated that Postn knockdown enhanced autophagic activity in cementoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively our data indicate that knockdown of Postn inhibits cementoblast mineralization in vitro. Growing evidence suggests that Postn has a regulatory effect on autophagy 21,22 ; thus, we examined the effects of Postn on autophagy in cementoblasts. Autophagy was upregulated with knockdown of Postn, as re ected by decreased levels of P62 and increased conversion of LC3-I to LC3-II (Fig.…”
Section: Knockdown Of Postn Inhibits Cementoblast Mineralizationmentioning
confidence: 99%
“…The results showed that the expression of the autophagy-related protein beclin 1 in osteoblasts was increased, suggesting that the autophagy function of osteoblasts was enhanced. This also indicates that POSTN inhibits autophagy in osteoblasts, although the specific signaling pathway mediating this effect has not yet been identified (83). In a subsequent study, these authors demonstrated that the protein expression of RUNX2 and RANKL was significantly reduced after POSTN gene silencing, and speculated that this process was achieved through the NF-κB signaling pathway (84).…”
Section: Activity Of Postn In Osteoblasts and Osteoclastsmentioning
confidence: 99%